2008
DOI: 10.1577/m06-254.1
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Responses of Rainbow Smelt to in situ Strobe Lights

Abstract: We conducted in situ testing of strobe lights as a potential fish deterrent by examining avoidance and acclimation behaviors of rainbow smelt Osmerus mordax in Lake Oahe, South Dakota. Split‐beam hydroacoustics were used to assess the effectiveness of the deterrent system by comparing proximal densities of rainbow smelt before and after the device was activated. In summer 2005, strobe lights successfully repelled rainbow smelt to a minimum horizontal distance of 21 m at both 1 h and 4 h postactivation; the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 9 publications
0
54
0
Order By: Relevance
“…Although it is unclear why some fishes are attracted to strobe lights, it has been hypothesized that strobe lights could potentially concentrate prey and/or increase feeding efficiency for visual-feeding fish (Johnson et al 2005). In Hamel et al (2008), rainbow smelt were deterred 15 m away from the strobe light in tests conducted in 2004. However, hydroacoustic estimates taken at distances farther than 15 m showed similar rainbow smelt densities as control estimates and may have increased in abundance after sustained operation (Hamel et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although it is unclear why some fishes are attracted to strobe lights, it has been hypothesized that strobe lights could potentially concentrate prey and/or increase feeding efficiency for visual-feeding fish (Johnson et al 2005). In Hamel et al (2008), rainbow smelt were deterred 15 m away from the strobe light in tests conducted in 2004. However, hydroacoustic estimates taken at distances farther than 15 m showed similar rainbow smelt densities as control estimates and may have increased in abundance after sustained operation (Hamel et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Hamel et al (2008), rainbow smelt were deterred 15 m away from the strobe light in tests conducted in 2004. However, hydroacoustic estimates taken at distances farther than 15 m showed similar rainbow smelt densities as control estimates and may have increased in abundance after sustained operation (Hamel et al 2008). Because cyclopoid and calanoid copepods and daphnid densities were reduced near the strobe lights in this study, it is unlikely that the attraction of fish to strobe lights found in other studies is due to concentration of zooplankton.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations